Prosedur Pemindahbukuan Pajak Pada Usaha Dengan Minimal Staf Accounting - Fransiska, Cindy; Sumarna, Alfonsa Dian (Jurnal Bisnis Mahasiswa, 2024)
Small and medium enterprises (SMEs) need practical guidance that can be applied to a limited scale of resources. In this case, tax deposit errors result in companies having to do tax transfers. The tax book-entry procedure is minor but can be significant if associated with delays in the overall tax compliance process. Therefore, a simple procedure will help SME businesses solve this problem smoothly. This descriptive research uses observation, documentation, interviews, and literature study. The purpose of this research is to develop a guideline in the form of a simple standard procedure for the process of transferring taxes, which can be easily applied to SMEs. The result of this study is a standard tax book-entry procedure in a step-by-step format and a flowchart format that can be chosen to be understood. So that employees in SME companies have a handle on the process so that there is no need for delays in transferring taxes due to employee ignorance.